Oncologic outcome after completing or abandoning (radical) hysterectomy in patients with cervical cancer and intraoperative detection of lymph node positivity; ABRAX (ABandoning RAd hyst in cerviX cancer). Issue 2 (20th November 2019) - Dostalek, Lukas; Runnebaum, Ingo; Raspagliesi, Francesco; Vergote, Ignace; Dusek, Ladislav; Jarkovsky, Jiri; Cibula, David
Abstract : Background: The management of patients with intraoperative detection of lymph node involvement remains controversial. The most significant aspect is the decision regarding the completion of the cervical procedure, such as hysterectomy, radical hysterectomy, or a fertility sparing procedure. Primary objective: The primary objective of the ABandoning RAd hyst in cerviX cancer (ABRAX) trial is to determine whether the completion of the cervical procedure (ie, radical hysterectomy) improves oncological outcome in patients with intraoperatively detected lymph node involvement before they are referred for definitive chemoradiation. Study hypothesis: We hypothesize that, in patients with intraoperative lymph node involvement, completion of radical hysterectomy or other cervical procedure does not improve the oncological outcome of definitive chemoradiation. Trial design: The ABRAX trial is a multicenter, retrospective, cohort study. Patients with negative lymph nodes in clinical staging, in whom lymph node involvement is detected intraoperatively, are included. Completion or abandonment of the planned cervical procedure stratifies the cohort into two subgroups in which oncological outcome and morbidity will be compared. Major Inclusion/Exclusion criteria: Patients with early stage (pT1a–pT2b) cervical cancer, who did not have positive lymph nodes on preoperative imaging, who were scheduled for primary surgical treatment, and in whom metastatic involvement of pelvic lymph node was found during surgery either as a grossly (macroscopically) involved or on intraoperative pathology assessment will be enrolled. Patients can be included irrespective of surgical approach (minimal invasive surgery or laparotomy) and type of cervical procedure performed (hysterectomy, radical hysterectomy, or a fertility sparing procedure). Primary endpoint: The primary endpoint of this retrospective study is a progression free survival in two subgroups with abandoned or completed cervical procedure followed by definitive chemoradiation in both groups. Sample size: The assumed sample size is 718 patients (in total for both groups). Estimated dates for completing accrual and presenting results: Estimated end of data collection: December 2019; estimated date of presenting results: Q2/3 2020. Trial registration: Clinicaltrials.gov: NCT04037124 .